Improving Motivation and Interpersonal Communication Skill ThroughPeer Assessment and Self-Assessment In Accounting Education Students - Sulikah, Sulikah; Nasikh, Nasikh (Universitas Negeri Malang, 2018)
This study aims at improving motivation and interpersonal communication skill through peer assessment and self-assessment in accounting education students.This study is conducted in Economic Faculty of the State University of Malang (Universitas Negeri Malang). The research subject is 160 undergraduate students of accounting education. This study is a classroom action research. The data collection is done by observation, interview, and documentation. The data are analyzed qualitatively by carrying out data reduction, data display, and verification processes. Research finding shows that peer assessment and self-assessment are able to improve motivation and communication skill of accounting education students in Economic Faculty of the State University of Malang.There is improvement in terms of learning motivation of students majoring accounting education in the teaching practice subject through peer assessment and self-assessment system, and there is improvement in terms of interpersonal communication skill of students majoring accounting education in the teaching practice subject through peer assessment and self-assessment system.